Trade‐offs between Tax and Financial Reporting Benefits: Evidence from Purchase Price Allocations in Taxable Acquisitions - Lynch, Daniel; Romney, Miles; Stomberg, Bridget; Wangerin, Daniel; Robinson, John R. (Contemporary Accounting Research, 2019)
ABSTRACT Under U.S. GAAP, firms recognize assets acquired in business combinations at fair value. Similarly, in taxable asset acquisitions firms adjust the tax basis of assets to fair value. Managers can increase the present value of future tax savings by allocating a greater portion of the purchase price to shorter‐lived assets than to goodwill or indefinite‐lived intangibles. However, this tax planning strategy imposes a financial reporting cost because it reduces book income following the acquisition; all else equal, allocations to shorter‐lived depreciable assets increase book depreciation expense, whereas allocations to goodwill and indefinite‐lived intangibles do not increase book amortization expense. We exploit the features of taxable asset acquisitions to investigate trade‐offs between tax and financial reporting incentives. We predict and find greater allocations to depreciable versus intangible assets when managers have strong tax incentives and weak financial reporting incentives. However, we also find that strong financial reporting incentives moderate the effects of strong tax incentives. These findings contribute new evidence to the literature on the importance of nontax costs in tax planning decisions